The Response of German Establishments to the 2008-2009 Economic Crisis - Bellmann, Lutz (OECD Social, Employment and Migration Working Papers, 2012)
We examine the response of a large panel of German establishments to the crisis in terms of their job flows (changes in employment) and consequent worker flows (hires, separations and layoffs). We analyse the extent to which job flows and worker flows at the establishment level are systematically related to institutional arrangements intended to promote flexibility such as Kurzarbeit (short-time work, STW) and Arbeitszeitkonten (working-time accounts, WTA). We find pronounced evidence of labour hoarding in the sense that labour productivity fell rapidly during the 2008-09 downturn, but we find no evidence that STW (or other policies) increased labour hoarding by reducing layoffs. This may well reflect the probable selection effects involved which are not accounted for by observable differences between STW and non- STW establishments